Performance Analysis Of Wireless Protocols Nstreme And Ieee 802.11 With Quality Of Service (Qos Parameters: A Case Study At Universitas Akprind Indonesia - Miftah Farid; Doni Wahyudi (Journal of Social Research, 2025)
This study aims to explore the wireless protocol mode in producing a stable bandwidth on a point-to-point network. In addition to obtaining stable bandwidth, this study also analyzes the values of throughput, jitter, delay, and packet loss according to Quality of Service. The research was conducted using a full-duplex method that can perform data transmission and data reception simultaneously without having to take turns. Testing was carried out using a MikroTik RouterBoard Metal 52ac device by testing the channel width on the 20 MHz, 20/40 MHz, and 20/40/80 MHz wireless interface configurations. The results obtained in this test show that the Nstreme protocol shows better throughput performance on the 20/40 MHz channel width with a throughput of 6368 Kbps with a delay of 1.4 ms and a jitter of 0.22 ms superior on the smaller channel width of 20 MHz. This happens because of the efficiency of the protocol in reducing overhead and interference. While the performance of the IEEE 802.11 protocol is also superior on the 20/40 MHz channel width with a throughput of 1881Kbps, with a delay of 2.5 ms and a jitter of 4.6 ms. Both protocols show better performance on the 20/40 MHz channel width than the 20/40/80 MHz due to their ability to use the wider spectrum more effectively and better utilize Multiple Input Multiple Output (MIMO) technology. For packet loss, both protocols show very low results, with the Nstreme protocol having better performance with 0.9991 % on the 20 MHz channel width. Meanwhile, the IEEE 802.11 protocol on the 20/40 MHz channel width shows a value of 0.9994 %. The research results with Quality of Service (QoS) parameters show a very good category according to the TIPHON standard.